Association of tumor necrosis factor-α promoter G-308A gene polymorphism with increased triglyceride level of subjects with metabolic syndrome - Mirhafez, Seyed Reza; Avan, Amir; Pasdar, Alireza; Kazemi, Elaheh; Ghasemi, Faezeh; Tajbakhsh, Amir; Tabaee, Samaneh; Ferns, Gordon A.; Ghayour-Mobarhan, Majid (Gene, 2015)
The G-308A single nucleotide polymorphism (SNP) in the promoter of tumor necrosis factor-alpha (TNF-α) gene has previously been reported to be associated with cardiovascular risk. However the potential association of this polymorphism with metabolic syndrome (MetS) is unclear. The aim of the current study was to explore the association of this TNF-α gene polymorphism with MetS in an Iranian population. Two hundred and twenty two subjects were recruited and anthropometric and biochemical parameters were determined. Genotyping was performed using the amplification refractory mutation system polymerase chain reaction. The association of the genetic-polymorphism with MetS was evaluated by univariate and multivariate analyses. MetS subjects had a significantly (P<0.05) higher level of fasted serum triglycerides, body-mass-index, waist-circumference, blood pressure and fasting-blood-glucose, and lower level of high-density lipoprotein cholesterol. The possession of AA or GA genotype of the TNF-α gene was not associated with MetS in our population. However the AA genotype of TNF-α was related to an increased level of triglyceride in MetS patients, compared to the control group. TNF-α G-308A polymorphism is unlikely to play an important role in the development of MetS in our population. •TNF-α-308G/A polymorphism is associated with insulin resistance and CVD.•This is the first study evaluating the role of TNF-α in Iranian MetS patients.•The AA genotype of TNF-α was associated with an increased level of triglyceride.